Road traffic accident fatalities and its association with key sociodemographic determinants in Nashik, Maharashtra: A recurring challenge - Tej Bahadur Chhetri; Syed Meraj Ahmed (Wolters Kluwer Medknow Publications, 2022)
Background: Road traffic accidents are not a new phenomenon, rather it's a disturbing occurrence which shows no sign of abating very soon. Rather, it remains one of those public health issues which even the most educated and civilized populations tend to ignore, primarily for the thrill of it. This study aims to identify the outcome associated with vehicular accidents and its association with socio-demographic factors. Method: This is a retrospective, record-based study of victims of road traffic accidents admitted in a tertiary care hospital in Nashik, Maharashtra. The data would include records from the 2018 to 2019. The variables will include the socio-demographic factors, site of injuries and its severity. A descriptive analysis would be done by SPSS software to find out the prevalence of vehicular accidents, association of site of injury with age and severity of the trauma. Ethical approval would be taken before the initiation of the study. Result: A total of 486 victims of RTAs were included from the medical records of the casualty of a tertiary care hospital, out of which 330 were from the year 2018 and 156 from 2019. A look at the sociodemographic profiles of the RTA victims showed that females comprised only 19.3% (2018) and 18.6% (2019) of the total victims in road traffic accidents, while majority, 80.6% (2018) and 81.4% (2019) were males during the same period. Overall, we can also observe that both in 2018 (38.5%) and 2019 (50.6%) most of the road traffic accidents among the victims were of moderate grade. Conclusion: The need of the hour is to bring about a change from within through self-reflection of lawmakers, strict implementation of traffic rules and guidelines with hefty fines, lockup, and criminal punishment to habitual wrongdoers.